UPAYA KONSERVASI LINGKUNGAN PADA KAWASAN INDUSTRI CANDI KOTA SEMARANG - Setyowati, Dewi Liesnoor (Indonesian Journal of Conservation, 2014)
The opening of Candi Industrial Area (KIC) resulted in hill cutting, deforestation, geological structure changes, the loss of two streams, the construction of warehousing with the stainless roof, installation, and construction of artesian wells. As a result, there is a problem of air, water, and soil pollution. The study was conducted in KIC. The data of land use was interpreted from Landsat TM imagery in 1994, and SPOT 5 imagery in 2006, as well as the field inspection in 2010. In General, there were changes in land use to residential and industrial. The extent of the settlement in 1994 amounted to 371.824 ha, in 2010, it was 486.350 ha, and 16,097 ha area of the industry in 1994 became 319.043 ha in 2010. Changes in land use had an impact on the increased value of peak discharge flow, amounting to 1,471 m3 / s in 1994, 3.338 m 3 / s in 2005, and in 2010 increased to 7.229 m3 / s. Conservation models are done in the upstream area of Silandak River. KIC must build green line with annual plants, a garden with shade trees, reservoirs or absorption pools, and absorption wells for every industry building and each residential plots of the industry. In the downstream area, it is essential to build solid embankments on the right and left side of the river. It is also important to construct proper drainage system to prevent the water stagnating. Last, planting trees which have strong roots durability is necessaryKeywords: land use, environmental conservation, industrial estates.Pembukaan Kawasan Industri Candi (KIC), mengakibatkan pemotongan bukit, penebangan pohon, perubahan struktur geologis, hilangnya dua aliran sungai, pembangunan pergudangan dengan atap steanless, pemasangan instalasi, dan pembuatan sumur artetis. Akibatnya terjadi permasalahan polusi udara, air, dan tanah. Penelitian dilakukan di KIC. Data penggunaan lahan diinterpretasi dari citra Landsat TM tahun 1994, dan citra SPOT 5 tahun 2006, serta ceking lapangan tahun 2010. Pada umumnya terdapat, perubahan penggunaan lahan menjadi pemukiman dan industri. Luas pemukiman tahun 1994 sebesar 371,824 Ha, tahun 2010 menjadi 486,350 Ha, luas industri 16,097 Ha tahun 1994, menjadi 319,043 Ha tahun 2010. Perubahan penggunaan lahan berdampak pada meningkatnya nilai debit puncak aliran, sebesar 1,471 m3/dt tahun 1994, pada tahun 2005 sebesar 3,338 m3/dt, dan tahun 2010 meningkat menjadi 7,229 m3/dt. Model konservasi dilakukan pada kawasan hulu Kali Silandak. KIC harus membangun jalur hijau, dengan tanaman tahunan, pembuatan taman dengan pohon pelindung, pembuatan embung atau kolam resapan, kewajiban membuat sumur resapan pada setiap bangunan industri, dan setiap kapling perumahan industri. Pada kawasan hilir sungai, dilakukan pembuatan tanggul, yang kokoh pada sisi kanan kiri sungai, pembuatan sistem drainase yang layak, supaya air tidak menggenang, sisi sungai ditanami tanaman yang mempunyai daya tahan akar yang kuat.Kata Kunci: penggunaan lahan, konservasi lingkungan, kawasan industri.